From Theory to Practice: Measuring end-of-life communication quality using multiple goals theory. Issue 5 (May 2017) - Van Scoy, L.J.; Scott, A.M.; Reading, J.M.; Chuang, C.H.; Chinchilli, V.M.; Levi, B.H.; Green, M.J.
Highlights: Multiple Goals Theory is a well-established communication framework. We applied this theory to measure the quality of end-of-life conversations. The methodology permits a nuanced and robust evaluation of communication quality. Our conversation quality analysis is a reliable, valid, and objective measure of communication. This methodology has potential for application to other communication contexts. Abstract: Objectives: To describe how multiple goals theory can be used as a reliable and valid measure (i.e., coding scheme) of the quality of conversations about end-of-life issues. Methods: We analyzed conversations from 17 conversations in which 68 participants (mean age = 51 years) played a game that prompted discussion in response to open-ended questions about end-of-life issues. Conversations (mean duration = 91 min) were audio-recorded and transcribed. Communication quality was assessed by three coders who assigned numeric scores rating how well individuals accomplished task, relational, and identity goals in the conversation. Results: The coding measure, which results in a quantifiable outcome, yielded strong reliability (intra-class correlation range = 0.73–0.89 and Cronbach's alpha range = 0.69–0.89 for each of the coded domains) and validity (using multilevel nonlinear modeling, we detected significant variability in scores between games for each of the coded domains, all p -values <0.02). Conclusions: Our coding scheme provides a theory-based measure of end-of-life conversation quality that is superior to other methods of measuring communication quality. Practice implications: Our description of the coding method enables researches to adapt and apply this measure to communication interventions in other clinical contexts.